Isolated Pulmonary Valvular Stenosis Noonan Syndrome A Case Report (University Heart Journal, 2010)
Noonan syndrome is an autosomal dominant dysmorphic characterized by hypertelorism, a downward eyeslant, and low-set posteriorly rotated ears. Other features include short stature, a short neck with webbing or redundancy of skin, cardiac anomalies, epicanthic fold, deafness, motor delay, and a bleeding diathesis. In this case report a 20 years male presented with severe pulmonary stenosis with classical sketetal abnomalities. Key words: Autosomal dominant; pulmonary stenosis DOI: 10.3329/uhj.v5i2.4564 University Heart Journal Vol.5(2) July 2009 pp.91-93